LC-MS/MS multiplex analysis of lysosphingolipids in plasma and amniotic fluid: A novel tool for the screening of sphingolipidoses and Niemann-Pick type C disease - Pettazzoni, Magali (PLoS One, 2017)
BACKGROUND: The biological diagnosis of sphingolipidoses currently relies on the measurement of specific enzymatic activities and/or genetic studies. Lysosphingolipids have recently emerged as potential biomarkers of sphingolipidoses and Niemann-Pick type C in plasma. METHODOLOGY: We developed a sensitive and specific method enabling the simultaneous quantification of lysosphingolipids by LC-MS/MS: lysoglobotriaosylceramide for Fabry disease, lysohexosylceramide (i.e. lysoglucosylceramide and/or lysogalactosylceramide) for Gaucher and Krabbe diseases, lysosphingomyelin and its carboxylated analogue lysosphingomyelin-509 for Niemann-Pick type A or B, and C diseases, lysoGM1 ganglioside for GM1gangliosidosis and lysoGM2 ganglioside for GM2 gangliosidosis. FINDINGS: The diagnostic performances were validated in plasma samples analysing a large series of patients affected with sphingolipidoses and Niemann-Pick type C disease (n = 98), other inborn errors of metabolism (n = 23), and controls (n = 228). The multiplex measurement of lysosphingolipids allowed the screening of Fabry (including female patients and late-onset variants), Gaucher and infantile Krabbe, Niemann-Pick type A/B and C diseases with high sensitivity and specificity. LysoGM1 and LysoGM2 were elevated in most of the patients affected with GM1 and GM2 gangliosidosis respectively. In amniotic fluid supernatant from pregnancies presenting non-immune hydrops fetalis (n = 77, including previously diagnosed Gaucher (n = 5), GM1 gangliosidosis (n = 4) and galactosialidosis (n = 4) fetuses) and from normal pregnancies (n = 15), a specific and dramatic increase of lysohexosylceramide was observed only in the Gaucher amniotic fluid samples. INTERPRETATION: This multiplex assay which allows the simultaneous measurement of lysosphingolipids in plasma modifies the diagnostic strategy of sphingolipidoses and Niemann-Pick type C. Furthermore, in pregnancies presenting non-immune hydrops fetalis, lysohexosylceramide measurement in amniotic fluid offers a rapid screening of fetal Gaucher disease without waiting for glucocerebrosidase activity measurement in cultured amniocytes.